A Library of ROS‐Catalytic Metalloenzyme Mimics with Atomic Metal Centers. Issue 16 (1st March 2022) - Cao, Sujiao; Zhao, Zhenyang; Zheng, Yijuan; Wu, Zihe; Ma, Tian; Zhu, Bihui; Yang, Chengdong; Xiang, Xi; Ma, Lang; Han, Xianglong; Wang, Yi; Guo, Quanyi; et al.
Abstract: MetalN‐coordinated centers supported by carbonaceous substrates have emerged as promising artificial metalloenzymes (AMEs) to mimic the biocatalytic effects of their natural counterparts. However, the synthesis of well‐defined AMEs that contain different atomic metalN centers but present similar physicochemical and coordination structures remains a substantial challenge. Here, 20 different types of AMEs with similar geometries and well‐defined atomic metalN‐coordinated centers are synthesized to compare and disclose the catalytic activities, substrate selectivities, kinetics, and reactive oxygen species (ROS) products. Their oxidase (OXD)‐, peroxidase (POD)‐, and halogen peroxidase (HPO)‐mimetic catalytic behaviors are systematically explored. The Fe‐AME shows the highest OXD‐ and HPO‐mimetic activities compared to the other AMEs due to its high v max (0.927 × 10 −6 m s −1 ) and low K m (1.070 × 10 −3 m ), while the Cu‐AME displays the best POD‐like performance. Furthermore, theoretical calculation reveals that the ROS‐catalytic paths and activities are highly related to the electronic structures of the metal centers. Benefiting from its facile adsorption of H2 O2 molecule and lower energy barrier to generating O2 −, the Fe‐AME displays higher ROS‐catalytic performances than the Mn‐AME. The engineered AMEs show not only remarkably high ROS‐catalytic performances but also provide new guidance toward developing metalN‐coordinated biocatalysts for broad application fields. Abstract : A library of reactive‐oxygen‐species (ROS)‐catalytic metalloenzyme mimics with 20 different types of atomic metal centers is synthesized to compare and disclose the catalytic activities, substrate selectivities, kinetics, and ROS products. These prepared biocatalysts not only show remarkably high ROS‐catalytic performances but also clearly reveal that the catalytic paths and activities are highly related to the electronic structures of metal centers.